'It's just absolutely everywhere': understanding LGBTQ experiences of queerbaiting. Issue 3 (3rd July 2022) - Woods, Nicole; Hardman, Doug
ABSTRACT: Queer media plays a significant role in the education and validation of emerging LGBTQ individuals. Although the volume of such media has increased, there are still ways in which it is misrepresentative. One such example is the practice of queerbaiting, which has been defined as media appearing but failing to provide allegiance to issues of queer visibility. Utilising phenomenological inquiry through application of semi-structured interviews, five university undergraduates who self-identified as LGBTQ described their experiences, thoughts, and feelings of queerbaiting. Consistent with prior research, participants felt that queerbaiting was an exploitative practice, which may have implications on identity development and acceptance. Opinions differed on what constitutes queerbaiting and the intentions of those who contribute to queerbaiting practice, suggesting that queerbaiting is a multi-dimensional phenomenon best understood as an umbrella term for diverse practices. From this we developed a new taxonomy of queerbaiting with three major forms: consumer queerbaiting; cultural queerbaiting; and social queerbaiting. Recognition of these three forms of queerbaiting may improve understanding of queerbaiting and its effects in future research and the diverse settings in which queerbaiting occurs.